An Analysis of Teachers’ Professional Competence in Utilizing ICT in SMPN 6 Poco Ranakan, East Manggarai the School Year of 2022/2023 (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is to find out how the professional competence of teachers in utilizing ICT in the teaching and learning process at SMPN 6 Poco Ranaka, East Manggarai. This research is qualitative research, using a qualitative descriptive design that describes the professional competence of teachers, especially in utilizing ICT in learning starting from the process of planning, implementing, and evaluating. There are ten teachers as the subject of this research. The data collection instruments used observation and interviews. In this study, researcher can conclude that in teaching preparation showed that there were only seven of ten teachers used ICT in classroom learning and they also prepared material and ICT services. Meanwhile, there were three teachers which are not ready to use ICT in the teaching preparation. In utilization while teaching process showed that seven of ten teachers who were ready to used ICT, but sometimes the teachers were used ICT only as needed because the ICT needs of each subject teacher are different. The last, in utilization in teaching evaluation activities showed that teachers used ICT in certain activities, such as keep an archive of students' daily grades by utilizing ICT, in the other side the teachers who were more dominant in using ICT during the evaluation were ICT subject teachers.